PENYULUHAN KESEHATAN TENTANG GIZI SEIMBANG DI POSYANDU BALITA KINASIH RW 29 WILAYAH KELURAHAN KADIPIRO SURAKARTA - Erinda Nur Pratiwi; Siti Nurjanah; Atiek Murharyati (Jurnal Salam Sehat Masyarakat (JSSM), 2020)
A health problem in Indonesia is the death of children under five years of age (toddlers). Based on the results of Basic Health Research, the prevalence of malnutrition under 5 years of age in Indonesia is 17.9% (3.7 million children under five), as many as 6800 children under five in East Java experience malnutrition, 25% of which is caused by malnutrition intake. Malnutrition status in toddlers can have an effect that greatly inhibits physical, mental and thinking skills which in turn will reduce work productivity. Balanced food at this age needs to be implemented because it will affect the quality at adulthood to advanced age so that community service is expected to improve the health status of toddlers. The goal of community service in the form of counseling on balanced nutrition is that after receiving the counseling, it is hoped that mothers with toddlers are able to instill good and correct eating habits in their children regarding balanced nutrition according to the needs for optimal child development, maintaining and increasing endurance. child against disease. The benefits of community service to increase knowledge, especially about balanced nutrition for toddlers according to the needs for optimal child growth and development so as to maintain and increase the child's resistance to disease. This community service method includes lectures, questions and answers and leaflet media. The results of the implementation of community service regarding balanced nutrition for toddlers show that toddlers' mothers understand better about balanced nutrition in toddlers with an average value of knowledge about balanced nutrition in toddlers with a percentage of 75%. The conclusion from this community service is that it is important for mothers under five to understand balanced nutrition in toddlers because it can improve the healthstatus of toddlers.